EFEKTIFITAS PENERAPAN SISTEM POIN PELANGGARAN DALAM UPAYA MENINGKATKAN KEDISIPLINAN PESERTA DIDIK DI MAN 1 PAREPARE - Samir , miranda (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
The violation point system is the imposition of sanctions or penalties for each rule violation committed by students by giving a number of points for each type of violation according to the type of violation committed by the student. The purpose of this activity is to: 1) improve the implementation of the payment system at MAN 1 Parepare; 2) Analyze the problems and solutions before implementing the system 3) Describe the effectiveness of implementing the violation system in an effort to improve student discipline at MAN 1 Parepare. Points of implementation of the MAN 1 Parepare system were used to test student discipline performance, which is a key factor in system design, according to the study's findings. For example, there is a teacher who does not participate in points when students are involved in discipline, parents of students who do not respond quickly to calls, and at least one student who cannot be divided, as well as a human resource (HR). This paper uses quantitative descriptive. using data processing techniques as follows: 1) Watching; (2) Interview (3) Documentation. From the results of the research that has been done, it can be concluded that the implementation of a staff behavior monitoring system is very effective in reducing the amount of time staff spend doing tasks because there are sanction points that assist staff in carrying out existing tasks. violation.